Adaptasi Pendidikan Islam Terhadap Perkembangan Teknologi dan Media Digital di Lembaga Pendidikan Islam - Fadli Rais; Nia Karnia; Rifalda Nur Ziyada; Rio Hidayatullah (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
The rapid development of technology and digital media has had a major impact on various aspects of life, including the world of education. In the context of Islamic learning, technology offers opportunities to improve the quality and effectiveness of teaching, but there are various challenges in its application. This research aims to analyze the application of technology in Islamic religious learning at SMPIT Buah Hati, with a focus on integrating Islamic values ​​in the use of digital media. This research uses a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The research subjects consisted of school principals, Islamic teachers, and students. The data obtained was analyzed using data reduction methods, data presentation and drawing conclusions, as well as ensuring the validity of the data through triangulation of sources and methods. The results of the research show that the application of technology in Islamic learning at SMPIT Buah Hati experiences various obstacles, such as limited digital devices, inadequate technical skills of teachers, and gaps in access to technology among students. However, students show high enthusiasm for technology-based learning, and teachers feel helped by digital applications. This research provides important implications for schools to improve technological infrastructure and provide intensive training for teachers, so that Islamic religious learning can be more effective and relevant in the digital era.